PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR PEMBELAJARAN IPA KELAS V SD - Wiro Aristo; Tahmid Sabri; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis reaearch aims to analyze the influence of the cooperative model audio-visual media in Social Science learning on the learning outcomes of  V grade Elementary School 03 in  Pontianak Kota. The method  used was experimental with Pre-Experimental Design and non equivalent control group design. The population of all students from two classes 54 people. the sample of this study was the students of VB class which amounted to 24 people as  experimental class and the VC class learners as  control class which amounted to 26 people. Data collection techniques used are measurement techniques and data collection tools was a written test of multiple choice. Based on the data analysis, the result of  average post-test of the experimental class class is 74,00 and the mean post-test control 70,50. Hypothesis test results using t-test (Polled Variance) obtained t count = 1,684 while for degree of freedom (24+26-2=48) with significant level α = 5% obtained t table = 1.676, which means t count > t table, this proves that there was influence of applying cooperative model of audio-visual media in Social Science learning. Based on the calculation of effect size (ES) obtained ES = 0.34which includes medium criteria.  Keywords: Audio Visual, Influence, Learning Outcomes, Science